NMR Signal Enhancement by Effective SABRE Labeling of Oligopeptides. Issue 36 (17th July 2015) - Ratajczyk, Tomasz; Gutmann, Torsten; Bernatowicz, Piotr; Buntkowsky, Gerd; Frydel, Jaroslaw; Fedorczyk, Bartlomiej
Abstract Signal amplification by reversible exchange (SABRE) can enhance nuclear magnetic resonance signals by several orders of magnitude. However, until now this was limited to a small number of model target molecules. Here, a new convenient method for SABRE activation applicable to a variety of synthetic model oligopeptides is demonstrated. For the first time, a highly SABRE‐active pyridine‐based biocompatible molecular framework is incorporated into synthetic oligopeptides. The SABRE activity is preserved, demonstrating the importance of such earmarking. Finally, a crucial exchange process responsible for SABRE activity is identified and discussed.